2007
DOI: 10.1021/jp072450k
|View full text |Cite
|
Sign up to set email alerts
|

Studying Reduction in Solid Oxide Fuel Cell Activity with Density Functional Theory− Effects of Hydrogen Sulfide Adsorption on Nickel Anode Surface

Abstract: To gain insight into the degree by which sulfur-based contaminants poison the solid oxide fuel cell (SOFC) anode, we examine adsorption and dissociation of consecutive molecules of hydrogen sulfide on a nickel (111) surface. Preferred adsorption sites, energies, transition states, and kinetic barriers are calculated for the resulting species, *SH x (x ) 0 -2) and *H. Systematically larger amounts of adsorbed sulfur (0, 25, 50, 75, 100%) are calculated to determine the most energetically favorable sulfur surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…Investigations of H 2 S adsorption on Cu(1 1 1) [73], Ni(1 1 1) [73,74] and Pt(1 1 1) [75] were previously carried out using DFT based on a (2 Â 2) slab (h H 2 S =1/4 ML). These studies also concluded that H 2 S binds through the S atom at a top site with the molecule sitting almost flat on the surface.…”
Section: Adsorption Of H 2 S Sh S and H On The Metal Surfacesmentioning
confidence: 99%
“…Investigations of H 2 S adsorption on Cu(1 1 1) [73], Ni(1 1 1) [73,74] and Pt(1 1 1) [75] were previously carried out using DFT based on a (2 Â 2) slab (h H 2 S =1/4 ML). These studies also concluded that H 2 S binds through the S atom at a top site with the molecule sitting almost flat on the surface.…”
Section: Adsorption Of H 2 S Sh S and H On The Metal Surfacesmentioning
confidence: 99%
“… Energy profiles for adsorption and subsequent dissociation of H 2 S on Ni and other metal surfaces. (Adapted from Galea et al 72 . (left) and Alfonso 73 (right).)…”
Section: Kinetic Predictionsmentioning
confidence: 99%
“…Galea et al have carried out similar calculations. 9 Wang and Liu calculated the variation of adsorption energy as function of surface coverage varying from −2.64 eV at 1/16 to −1.40 eV at 10/16 .…”
Section: Chemisorption Of Sulfur On Nickelmentioning
confidence: 99%